Experimental and numerical evaluation of the performances of electromagnetic miniature energy harvesters driven by air flow - Han, Nuomin (2017)
An increasing concern for energy safety and environmental sustainability has shifted energy research focus to renewable energy sources. Among these energy sources, wind energy has great potential to be harnessed. Most of natural wind energy harvesting is achieved from large scale wind turbines, which are located in less populated areas. However, there are ‘man-made’ wind resources being neglected or wasted in tropical countries such as Singapore, such as those associated with heating, ventilation and air conditioning (HVAC) systems. Thus there is a need for developing and manufacturing energy-efficient miniature wind energy harvesters. The present work considers the design and optimization of miniature electromagnetic energy harvesters driven by air flow. For this, both experimental and numerical investigations are performed. 10 energy harvesters are designed and fabricated by using 3D printing technology as modified versions of Savonius wind turbines coupled with an electromagnetic generator. Their axes of rotation were parallel to the ground but perpendicular to the wind flow direction. The performances of these energy harvesters are evaluated in a closed-loop wind tunnel in the Aerodynamics Laboratory, Nanyang Technological University in terms of total electrical power and overall energy conversion efficiency. Preliminary parametric measurements are conducted to investigate the effects of 1) the blade number, 2) the geometric size, 3) the aspect ratio, 4) the types of central part, 5) end plates and 6) the orientation of the energy harvester. An optimum design of the miniature energy harvester is obtained in terms of the maximum overall energy conversion efficiency (ηmax). The optimum harvester is shown to be associated with maximum efficiency of ηmax=6.59%. It is a 3-semi-cylindrical-blade energy harvester with size ratio of one, aspect ratio of one, solid central shaft, end plates at both ends and installed with an ‘anti-clockwise’ orientation. Comparison is then made with the commercially widely used horizontal-axis wind turbines with similar dimensions. To simulate the experiments, 3D numerical simulations are conducted by using ANSYS CFX. The numerical model is validated first by comparing with the experimental results. Finally, the model is used to evaluate the static and dynamic performances of these harvesters and to optimize the harvester’s orientation and blade shape. In summary, miniature 3D printed electromagnetic energy harvesters driven by air flow are systematically studied. It has been shown that these energy efficient harvesters have great potential to be applied in HVAC systems.